International Data Spaces : a collaborative organizational moonshot - Chesbrough, Henry William, (SAGE Business cases., 2021)
Reinhold Achatz, the Thyssenkrupp CTO, has been asked by the German Ministry of Education to lead the nonprofit organization IDSA to set, diffuse, and implement a dominant global B2B data standard. IDSA was steadily developing the standard in strong collaboration with the Fraunhofer and several industrial partners. After overcoming the initial overactivity of the industrial partners who wanted to set up their own data standards, the working groups were steadily progressing, and the launching coalition started to develop their standard rulebook and the amount of EU-funded projects based on the standard-reference architecture was growing.However, in 2019 the sister organization GAIA X was established by another German Ministry of Economics in collaboration with its French counterpart. It aimed to set up a European Cloud. GAIA X was born international and even without any technology, it has attracted much more attention both within and outside Germany than IDSA. The hype was so big that after nearly two years everyone was talking about the visionary approach of GAIA X which was labeled as the 'Moonshot in digital politics'. Yet, without IDSA's hard work of the last 5 years, GAIA X would have nothing to build upon.Achatz slowly starts to realize that even a brilliant technology of the future will not sell itself on its own merits. To fulfill the assignment given by the Ministry of Education he needs to decide how open the data standard and related collaborative activities should be to encourage wide standard adoption while maintaining the identity and legacy of the IDSA that has been building over the last 5 years.